2003
DOI: 10.4049/jimmunol.170.11.5429
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Vα14Jα18 Natural T Cell Number and Function in Autoimmune-Prone Mice

Abstract: Nonobese diabetic (NOD) mice, a model for type I diabetes (TID), have reduced numbers of invariant Vα14Jα18 TCR α-chain-positive natural T (iNKT) cells that do not release IL-4 in response to in vivo activation through their Ag receptor. The deficit in iNKT cell number and function is implicated in immune dysregulation and the etiology of TID. Therefore, we reasoned that the genetic determinant(s) that controls iNKT cell number and function might lie within Idd (insulin-dependent diabetes susceptibility locus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 58 publications
4
62
0
Order By: Relevance
“…25 NOD genes contributing to this immunodeficiency have been reported in the Idd4, Idd5, Idd9.1 and Idd13 regions, regions distinguishing NOR from NOD. 26,27 Certain of the immune anomalies associated with NOD antigen-presenting cells (APC) also are more normal in NOR, including NF-kB regulation that promotes more normal control of IL-12p70, TNFa and IL-1a cytokine secretion. 28 Thus, a combination of NOR genes serve to suppress autoimmune diabetes development at both the T-cell and APC levels.…”
Section: Discussionmentioning
confidence: 99%
“…25 NOD genes contributing to this immunodeficiency have been reported in the Idd4, Idd5, Idd9.1 and Idd13 regions, regions distinguishing NOR from NOD. 26,27 Certain of the immune anomalies associated with NOD antigen-presenting cells (APC) also are more normal in NOR, including NF-kB regulation that promotes more normal control of IL-12p70, TNFa and IL-1a cytokine secretion. 28 Thus, a combination of NOR genes serve to suppress autoimmune diabetes development at both the T-cell and APC levels.…”
Section: Discussionmentioning
confidence: 99%
“…As no NKT cell defects were reported in B6.Sle2 mice, the NZB region can be further localized to a 12.1-100.5 Mb interval indicating that the B1a phenotype can be genetically dissected from the NKT cell phenotype (15). Interestingly, NOD congenic studies have identified a locus, Idd9.1 (88.0 -135.8 Mb), which controls the number of NKT cells on chromosome 4 (38). Generation of additional subcongenic mice will be required to determine whether the observed NKT cell phenotype arises from the same genetic locus.…”
Section: Discussionmentioning
confidence: 99%
“…thymocytes and cocultured in triplicate for 18 -20 h at 37°C. IL-2 secreted upon activation of the hybridoma was monitored by ELISA (9).…”
Section: C57bl/6 and B6129-nf-b1mentioning
confidence: 99%
“…with 10 g of ␣GalCer diluted in PBS from a 200 g/ml stock solution in vehicle (0.05% v/v polysorbate-20 and 0.9% w/v NaCl) or vehicle. Four hours later, sera were collected, and IL-2, IL-4, and IFN-␥ were measured by ELISA (9).…”
Section: Measurement Of Cytokine Responsesmentioning
confidence: 99%